Hysterosalpingographic Evaluation of Infertile Women in Tertiary Care Center - Manandhar, Rojina; Rauniyar, Nabin K.; Joshi, Santosh; Singh, Sabita; Shrestha, Usha; Pathak, Punam (Grande Medical Journal, 2025)
Background Infertility refers to a inability of couple to achieve pregnancy after one year of consistent, unprotected intercourse. Conditions involving the fallopian tubes are responsible for an estimated 35–40% of female infertility cases. Hysterosalpingography (HSG) offers a cost-effective method to assess the patency of the fallopian tubes and the structure of the uterus. This study aims to examine the frequency of abnormal uterine and tubal findings among infertile women undergoing HSG at Nepal Police Hospital. Method This is a retrospective study done in Nepal Police Hospital from from 1st July 2023 till 31st December 2024. It has included all women with a history of primary or secondary infertility coming for infertility assessment and had undergone HSG during that period. HSG examination was done during the follicular phase of menstrual cycle, between 6 and 11 cycle day. It was conducted by gynaecologist under the supervision of experienced radiographer. The findings analyzed by experienced radiologists and kept in hospital records Data regarding information about the patients and HSG findings were obtained from hospital records and entered in MS-Excel were processed and interpreted using IBM SPSS Statistics software, version 22.0. Result A total 112 women were included in the study. Age of the patients ranged from 21 to 40 years The mean age of patients was 29 years with maximum (41.07%) of them belonging to the age group of 26- 30 years. Out of the total, 82 women (73.21%) were diagnosed with primary infertility, whereas 30 (26.7%) had secondary infertility. HSG abnormalities were seen in 28 patients (25%). Abnormal HSG finding was more common in primary infertility (78.57 %) than in secondary infertily (21.4%). Among HSG findings, tubal abnormalities were most common, identified in 20 patients (17.85%), followed by uterine anomalies in 4.46% and a combination of uterine and tubal abnormalities in 2.6% of cases. The most common tubal abnormality detected on HSG was tubal block seen in 82.6% of the total. A single tubal blockage was identified in 73.9% of cases, while bilateral tubal blockages were found in 8.6%. Uterine abnormalities seen in 7.14% (8/112). Among all uterine abnormalities, two uterine cavity is most common(37.5%). Conclusion HSG is an easy, relatively safe and cost effective procedure which can diagnose most structural cause of infertility i.e. uterine and tubal abnormalities. So, invasive procedures like laparoscopy and hysteroscopy are not indicated in patients with normal HSG findings. Hence it can minimize the use of invasive procedures and patients may be managed conservatively. It also increases the probability of conception by opening up flimsy adhesion.